EFFECT OF HEALTH PROMOTION INTERVENTION IN IMPROVING THE QUALITY OF LIFE AMONG PHYSICALLY CHALLENGED CHILDREN: A SCHOOL BASED INTERVENTIONAL STUDY - MAHARAJ SINGH,; DR.P.PARAMANANDAM, (International Journal of Pharma and Bio Sciences, 2015)
Children living with disability are often at increased risk for the development of secondary conditions that can lead to further decline in functional status, health status and overall quality of life. The aim of this study was to evaluate the effectiveness of health promotion intervention in improving the quality of life among physically challenged children. The total 120 samples were selected through purposive sampling technique from selected special schools, out of which 60 were in experimental and 60 were in control group. The experimental group received health promotion intervention for the duration of 36 weeks, but the control group remained without this. The quality of life was assessed using quality of life questionnaire at baseline, 12th, 24th and 36th week. There was statistically significant and very highly significant difference found at 12th week (p=0.04), 24th week (p= 0.001), and 36th week (p= 0.001) in physical wellbeing, psychological wellbeing, social wellbeing and overall quality of life values between the experimental and control group. Hence health promotion intervention is cornerstone in improving the quality of life among physically challenged children.